Vegan Food Business Under Green Economy Towards Sustainability - Saengmaneedech, Thirawut; Thammawimutti, Apiluck; Visesprapa, Prapassorn (KKBS Journal of Business Administration and Accountancy, 2025)
This academic paper aimed to 1. analyze the growth of vegan business as an alternative food in accordance with green economy, which focuses on creating added value through innovation and sustainability, 2. analyze the factors affecting the growth and challenges of the vegan food business, and 3. propose guidelines for developing vegan food business and industry for sustainable growth based on the principles of the green economy and economic, social and environmental benefits. The vegan food market had the opportunity to grow continuously and was expected to increase its market value in the future. Supporting vegan food business and industry to grow in accordance with green economy would help achieve sustainable goals. Based on the analysis, the factors affecting the growth and challenges of vegan food business are (1) consumers’ values, beliefs and attitudes towards vegan food, (2) the trend of Go Green and environment protection and (3) the development of technology and innovation. Vegan food was considered as an alternative food that supported green economy. If consumers, as the main stakeholders, started to consume more vegan food instead of meat in their daily lives, it would help solve greenhouse gases and carbon dioxide emissions caused by livestock processes. Stakeholders should practice the proposed vegan business and industry development guidelines that aligned with the five key principles of the green economy for the sustainable growth of vegan business and industry.